Creation of a Petty Cash Management Information System Based on Microsoft Access in the Marketing and Sales Division of PT Pindad - Vania Tusyadiyah; Maya Setiawardani (Ebiz Prima Nusa, 2024)
PT Pindad is a state-owned company engaged in the production of defense equipment. This company has three branch offices spread throughout Indonesia, one of which is located in Bandung. The Bandung branch of PT Pindad has various divisions, one of which is the Marketing and Sales Division. in the Marketing and Sales Division, in managing petty cash, they still use Microsoft Excel, which still has some drawbacks, namely the recording process still has to be recorded three times, namely having to record petty cash vouchers per transaction, then it is recorded back into the book of recording receipts and disbursements of temporary petty cash. After recording the receipt and disbursement of temporary petty cash from the record book, it is then recorded back into the petty cash report book, so it takes quite a long time. Filling in petty cash vouchers is still filled in manually. Evidence of petty cash disbursements in the form of receipts, notes and receipts are kept in drawers and scattered around, so if needed it takes a long time to find the evidence. Based on these problems, a petty cash management information system based on Microsoft Access was designed to make it easier for employees to manage petty cash. After testing, it was found that creating a petty cash management information system can make it easier for petty cash holders to manage petty cash.